Scribal culture in Ben Sira - Askin, Lindsey A. (Journal for the study of Judaism / Supplements, 2018)
"In Scribal Culture in Ben Sira, Lindsey A. Askin examines scribal culture as a framework for analysing features of textual referencing throughout the Book of Ben Sira (c.198-175 BCE), revealing new insights into how Ben Sira wrote his book of wisdom. Although the title of "scribe" is regularly applied to Ben Sira, this designation presents certain interpretive challenges. Through comparative analysis, Askin contextualizes the sage's compositional style across historical, literary, and socio-cultural spheres of operation. New light is shed on Ben Sira's text and early Jewish textual reuse. Drawing upon physical and material evidence of reading and writing, Askin reveals the dexterity and complexity of Ben Sira's sustained textual reuse. Ben Sira's achievement thus demonstrates exemplary, "excellent" writing to a receptive audience"--